Gravity waves above Andes detected from GPS radio occultation temperature profiles: Mountain forcing? - de la Torre, A. (2005)
A significant wave activity in the upper troposphere and lower stratosphere at midlatitudes (30-40S) above the Andes Range was recently detected from Global Positioning System Radio Occultation (GPS RO) temperature profiles, retrieved from SAC-C (Satélite de Aplicaciones Cientficas-C and CHAMP (CHAllenging Minisatellite Payload) satellites. Previously, large amplitude, long vertical wavelength structures have been reported in this region, as detected from other limb-sounding devices and have been identified as mountain waves (MWs). The capability of GPS RO observations to detect typical MWs with horizontal wavelengths shorter than 150 km, as well as the proper association of the observed wave activity to mountain forcing is put in doubt. Other three possible sources are discussed. In particular, the generation of inertio-gravity waves by geostrophic adjustment near to a permanent jet situated above the mountains, may constitute another important mechanism in this region. These waves may possess longer horizontal and perhaps shorter vertical wavelengths than those typically expected in MWs and could be more easily detected from limb-sounding profiles. The "jet" mechanism will be discussed in a second paper. Copyright 2005 by the American Geophysical Union.